Inhibitory Effects Of Edible Seaweeds, Polyphenolics and Alginates On The Activities Of Porcine Pancreatic α-amylase - Nazikussabah, Zaharudin; Salmeán, Armando Asunción; Dragsted, Lars Ove (Elsevier, 2017)
Edible seaweeds are valuable because of their organoleptic properties and complex polysaccharide content. A study was conducted to investigate the potential of dried edible seaweed extracts, its potential phenolic compounds and alginates for α-amylase inhibitory effects. The kinetics of inhibition was assessed in comparison with acarbose. The methanol extract of Laminaria digitata and the acetone extract of Undaria pinnatifida showed inhibitory activity against α-amylase, IC50 0.74 ± 0.02 mg/ml and 0.81 ± 0.03 mg/ml, respectively; both showed mixed-type inhibition. Phenolic compound, 2,5-dihydroxybenzoic acid was found to be a potent inhibitor of α-amylase with an IC50 value of 0.046 ± 0.004 mg/ml. Alginates found in brown seaweeds appeared to be potent inhibitors of α-amylase activity with an IC50 of (0.075 ± 0.010–0.103 ± 0.017) mg/ml, also a mixed-type inhibition. Overall, the findings provide information that crude extracts of brown edible seaweeds, phenolic compounds and alginates are potent α-amylase inhibitors, thereby potentially retarding glucose liberation from starches and alleviation of postprandial hyperglycaemia.